Families, Income and Jobs, Volume 6: A Statistical Report on Wave 1 to 8 of the Household, Income and Labour Dynamcis in Australia Survey - Wilkins, R; Hahn, M; Houng, B; Warren, D (My University, 2011)
Volume 6 of the Statistical Report is based on the first eight waves of data collected by the HILDA Survey and comprises two parts. Part A contains short articles that provide an annual update of changes in key aspects of life in Australia, covering the four main areas of HILDA, namely: Households and family life; Incomes and economic wellbeing; Labour market outcomes; and Life satisfaction, health and wellbeing. The second part of the report, Part B, contains articles on irregular topics, to a significant extent influenced by wave-specific questions included in the survey.
Families, Incomes and Jobs
HILDA Statistical Reports
Keywords: Finance -- Income (Salary and Wages); Employment; Families; Finance; Surveys and Survey Methodology; Surveys and Survey Methodology; Families and relationships; Income, wealth and finances; Employment; Finance; Families; Surveys and Survey Methodology; Income (Salary and Wages); Income, wealth and finances; Families and relationships